INTEGRASI DAN KAUSALITAS HARGA CABAI RAWIT: ANALISIS EMPIRIS PASAR PRODUSEN DAN KONSUMEN JAWA TIMUR. - Imama Nurus Izaati; Azwar Annas; Iid Mufaidah (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2026)
This study aims to market integration and causality of cayenne pepper price transmission between producer and consumer markets in East Java. Producer markets are represented by Kediri and Malang Regencies, while consumer markets are represented by Surabaya and Malang City. The analysis method used is Vector Autoregression (VAR), considering the dynamics of short-term relationships between markets. The results show high price persistence across markets, reflecting the strong influence of previous period prices on current prices. Furthermore, there is strong vertical market integration, with producer markets acting as price leaders, significantly influencing consumer markets, particularly in Surabaya. Conversely, the influence of consumer markets on producer markets is relatively limited, indicating a more supply-driven market system. These findings also reveal interconnected consumption across markets, indicating spatial competition. Overall, this study provides empirical evidence that cayenne pepper markets in East Java are spatially and vertically integrated, and emphasizes the strategic role of producer markets in price formation and transmission between regions.